2018
DOI: 10.1021/acs.jafc.8b04810
|View full text |Cite
|
Sign up to set email alerts
|

PpMYB15 and PpMYBF1 Transcription Factors Are Involved in Regulating Flavonol Biosynthesis in Peach Fruit

Abstract: Flavonoids are major polyphenol compounds in plants and contribute substantially to the health-promoting benefits of fruit and vegetables. Peach is rich in polyphenols with flavonols as the main flavonoids. To investigate the regulation of flavonol biosynthesis in peach fruit, two R2R3-MYB transcription factor (TF) genes, PpMYB15 and PpMYBF1, were isolated and characterized. Sequence analysis revealed that the PpMYB15 and PpMYBF1 proteins are members of the flavonol clade of the R2R3-MYB family. Real-time quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 36 publications
2
65
0
Order By: Relevance
“…Flavonols was extracted according to our previous report with minor modication. 27 The lyophilized powder of Chinese bayberry pulp (1 g) was dissolved in 10 mL of 80% aqueous methanol with sonication for 30 min, centrifuged at room temperature (12 000 rpm, 15 min) and the residue was extracted again as above. Supernatants were then combined and evaporated under reduced pressure at 37 C by a rotary evaporator.…”
Section: Flavonols Extraction From Chinese Bayberrymentioning
confidence: 99%
“…Flavonols was extracted according to our previous report with minor modication. 27 The lyophilized powder of Chinese bayberry pulp (1 g) was dissolved in 10 mL of 80% aqueous methanol with sonication for 30 min, centrifuged at room temperature (12 000 rpm, 15 min) and the residue was extracted again as above. Supernatants were then combined and evaporated under reduced pressure at 37 C by a rotary evaporator.…”
Section: Flavonols Extraction From Chinese Bayberrymentioning
confidence: 99%
“…Furthermore, PsMYB114L had a bHLH-interaction motif ([D/E]Lx2[R/K]x3Lx6Lx3R) in the R3 domain at the N terminus and did not have any conserved motifs at the C terminus (Figure 2A). Moreover, PsMYB12L did not have any bHLH-interaction motifs at the N terminus, whereas it contained two flavonol-specific motifs [40], namely, SG7 ([K/R][R/x][R/K]xGRT[S/x][R/G]xx[M/x]K) and SG7-2 ([W/x][L/x]LS), at the C terminus (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Ectopic expression analysis of EsMYBF1 in transgenic tobacco indicated that NtCHS , NtCHI , NtF3H , and NtFLS were upregulated but NtDFR and NtANS were significantly downregulated, and the accumulation of anthocyanins in transgenic tobacco flowers was also remarkably decreased [63]. A study on the overexpression of PpMYB15 in tobacco showed that it can significantly activate the expression of NtCHS , NtCHI , NtF3H , and NtFLS , while it had no effects on the expression of NtDFR and NtANS , resulting in pale-pink or pure white flowers in transgenic tobacco plants [40]. Compared with the expression of anthocyanin biosynthesis-related genes documented in the abovementioned studies, in this study AtCHS/MdCHS , AtCHI , AtF3H/MdF3H , and AtFLS had a somewhat similar expression pattern and MdFLS , AtDFR/MdDFR and AtANS/MdANS exhibited the opposite pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [27] found signi cant differences in the avonoid components and contents among 3 strains, i.e., Hongcui NO.1, Hongcui NO.2 and Hongcui NO.4, which might result from variations in the expression of transcription factors and the structure of genes related to avonoid biosynthesis. Cao et al [40] found that PpMYB15 and PpMYBF1 were involved in regulating avonol biosynthesis in peach fruit. In the present study, based on the results of whole-transcriptome sequencing, GO enrichment analysis and KEGG pathway enrichment analysis, 8 DEGs related to avonoid biosynthesis, namely, CYP98A2 (1), CYP98A2 (2), BADH, DAT, MdHCT (1), MdHCT (2), CHI (1) and CHI (2), were selected for validation of their differential expression in JKG vs. BG, JKG vs BGBB and JKG vs JKBF by qRT-PCR analysis.…”
Section: Discussionmentioning
confidence: 99%